2023
DOI: 10.1002/smll.202300750
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Single‐Atom Nanozymes for Catalytic Biomedical Applications

Abstract: Nanomaterials with enzyme‐mimicking properties, coined as nanozymes, are a promising alternative to natural enzymes owing to their remarkable advantages, such as high stability, easy preparation, and favorable catalytic performance. Recently, with the rapid development of nanotechnology and characterization techniques, single atom nanozymes (SAzymes) with atomically dispersed active sites, well‐defined electronic and geometric structures, tunable coordination environment, and maximum metal atom utilization are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 174 publications
0
25
0
Order By: Relevance
“…Therefore, the utilization of surface engineering can enhance the performance of SAzymes in specific physiological environments by improving water dispersion, targeting ability, catalytic efficiency, immunogenicity, and prolonging circulation time. 136…”
Section: Regulation Strategy Of Sazyme Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the utilization of surface engineering can enhance the performance of SAzymes in specific physiological environments by improving water dispersion, targeting ability, catalytic efficiency, immunogenicity, and prolonging circulation time. 136…”
Section: Regulation Strategy Of Sazyme Activitymentioning
confidence: 99%
“…In contrast, natural OXD can activate O 2 molecules to produce ROS without the need for additional H 2 O 2 , making them more versatile catalysts for oxidation reactions. 178,179 Recently, some SAzymes have been found to exhibit oxidase-like activity. 180–183…”
Section: Design Strategy and Catalytic Mechanism Of Sazymesmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Owing to the adjustable coordination environment and electronic structure of the metal site, single-atom nanozymes (SAzymes) exhibit a diverse range of enzyme-like catalytic activities, including peroxidase (POD), oxidase (OXD), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx). 20 Thus far, SAzymes have been successfully applied in the treatment of cancer, bacterial infections, and oxidative stress-related diseases. 21,22 Although several outstanding reviews have summarized the development of SAzymes in the field of biomedicine, 23,24 no specific review pertaining to antibacterial treatment has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Realizing efficient and less toxic treatments for cancer is always the focus of research . Together with the development of nanomedicine, nanocatalytic therapy provides new perspectives for the treatment of cancer. , Catalytic therapy mainly involves a chemical reaction in situ within the tumor with catalytically active nanomaterials to produce toxic substances to kill tumor cells. , Nanozymes are attracting widespread attention in the field of catalytic medicine since they contain the catalytic activity of natural enzymes and the physicochemical properties of nanomaterials. In recent years, multiple nanozymes are emerging, including carbon-based nanozymes, iron-based nanozymes, manganese-based nanozymes, , and single-atom nanozymes, which are widely used for detection, disease therapy, and especially nanozyme-mediated tumor catalytic therapy. …”
Section: Introductionmentioning
confidence: 99%